Assessing the Impacts of Extreme Agricultural Droughts in China Under Climate and Socioeconomic Changes. Issue 5 (8th May 2018) - Yu, Chaoqing; Huang, Xiao; Chen, Han; Huang, Guorui; Ni, Shaoqiang; Wright, Jonathon S.; Hall, Jim; Ciais, Philippe; Zhang, Jie; Xiao, Yuchen; Sun, Zhanli; Wang, Xuhui; et al.
Abstract: Agricultural food production in China is deeply vulnerable to extreme droughts. Although there are many studies to evaluate this issue from different aspects, comprehensive assessments with full consideration of climate change, crop rotations, irrigation effects, and socioeconomic factors in broad scales have not been well addressed. Considering both the probability of drought occurrence and the consequential yield losses, here we propose an integrated approach for assessing past and future agricultural drought risks that relies on multimodel ensemble simulations calibrated for rice, maize, and wheat (RMW) in China. Our results show that irrigation has reduced drought‐related yield losses by 31 ± 2%; the largest reductions in food production were primarily attributable to socioeconomic factors rather than droughts during 1955–2014. Unsustainable water management, especially groundwater management, could potentially cause disastrous consequences in both food production and water supply in extreme events. Our simulations project a rise of 2.5~3.3% in average rice, maize, and wheat productivity before 2050 but decrease thereafter if climate warming continues. The frequency of extreme agricultural droughts in China is projected to increase under all examined Representative Concentration Pathway (RCP). A current 100‐year drought is projected to occur once every 30 years under RCP 2.6, once every 13 years under RCP 4.5, and once every 5 years under RCP 8.5. This increased occurrence of severe droughts would double the rate of drought‐induced yield losses in the largest warming scenario. Policies for future food security should prioritize sustainable intensification and conservation of groundwater, as well as geographically balanced water resource and food production. Key Points: The development of irrigation in China has alleviated negative drought impacts on food productivity, the presence of irrigation systems explaining 31 ± 2% of avoided yield loss Frequency and intensity of extreme droughts are projected to increase significantly under future climate change, leading to double the drought‐induced yield losses in the largest warming scenarios The sharpest drops in grain production during the past 60 years have been driven primarily by socioeconomic disturbances rather than by large droughts